Assessment of Autonomic Nerve Function In Hypothyroids By Time Domain Method of Heart Rate Variability - Ahmed, Matia; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2012)
Background: Cardiovascular complications are common in hypothyroids .Time domain measures of HRV is useful to determine the cardiac autonomic regulation by assessing sympathovagal balance. Objective: To assess the cardiac autonomic nerve function activity by time domain measures of heart rate variability in patients with hypothyroidism. Methods: This cross sectional study was carried out in the Department of Physiology, Banghabandhu Sheikh Mujib Medical University between July 2008 to June 2009 on 60 female patients with hypothyroidism aged 30-50 years. 30 age matched apparently healthy euthyroid subjects were also studied as control. Hypothyroid patients were divided into 2 subgroups, one group includes patients on their 1st day of diagnosis, before starting of treatment and another group includes patients with medication for 12-18 months. The patients were selected from the Out Patients Department of Endocrinology Wing BSMMU. Serum TSH and FT4 levels of all subjects were measured by AxSYM system. For assessing HRV by time domain method, mean R-R interval, mean heart rate, SDNN, RMSSD and variance were measured by a Polyrite. For statistical analysis, Independent Sample t test and One Way ANOVA were used. Results: The mean serum TSH was significantly higher and FT4 was significantly lower (p<0.001) in newly diagnosed hypothyroids than those of control and treated group. In untreated hypothyroid patients the mean values of heart rate, SDNN, RMSSD,variance were found significantly (p<0.001) lower in comparison to both control and treated patients. No significant difference in these hormonal levels and all these time domain measures were found between control and treated group. Conclusion: This study concludes that decrease parasympathetic nerve activity may be a consequence of hypothyroidism, if not treated properly. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11162 J Bangladesh Soc Physiol. 2012, June; 7(1): 48-52